Belt and Road Initiative: Five Years on Implementation and Reflection. (January 2019) - Hu, Biliang
This article summarizes the implementation of the Belt and Road Initiative (BRI), which was carried out 5 years ago. To date the basic institutional framework has been set up, some key infrastructural projects launched; joint development zones established and supporting systems have been set up to ensure the smooth infrastructure development of BRI. This article also explains the important factors why China proposed and implemented the initiative: accelerating world economic growth particularly for the developing countries, promoting economic globalization, improving global governance, and supporting UN Agenda 2030 for sustainable development. Based on the 5 years' experience of the Belt and Road implementation, the initiative reflects correctly the mega trend of world development and global cooperation, as well as the common interests of China and other relevant participating countries. A promising future for the initiative is most likely; however, careful feasibility study for investments is required to manage debt risk well for both the investors and the receivers of the investments.